A Population Survey in Italy Based on the ICF Classification: Recognizing Persons with Severe Disability. (1st February 2012) - Leonardi, Matilde; Martinuzzi, Andrea; Meucci, Paolo; Sala, Marina; Russo, Emanuela; Buffoni, Mara; Raggi, Alberto
Abstract : Aim of this paper is to describe functioning of subjects with "severe disability" collected with a protocol based on the International Classification of Functioning, Disability, and Health. It included sections on body functions and structures (BF and BS), activities and participation (A&P), and environmental factors (EF). In A&P, performance without personal support (WPS) was added to standard capacity and performance. Persons with severe disability were those reporting a number of very severe/complete problems in BF or in A&P-capacity superior to mean + 1SD. Correlations between BF and A&P and differences between capacity, performance-WPS, and performance were assessed with Spearman's coefficient. Out of 1051, 200 subjects were considered as severely disabled. Mild to moderate correlations between BF and A&P were reported (between 0.148 and 0.394 when the full range of impairments/limitations was taken into account; between 0.198 and 0.285 when only the severe impairments/limitations were taken into account); performance-WPS was less similar to performance than to capacity. Our approach enabled identifying subjects with "severe disability" and separating the effect of personal support from that of devices, policies, and service provision.